Haenamindole, an unusual diketopiperazine derivative from a marine-derived Penicillium sp. KCB12F005. Issue 22 (15th November 2015) - Kim, Jong Won; Ko, Sung-Kyun; Son, Sangkeun; Shin, Kee-Sun; Ryoo, In-Ja; Hong, Young-Soo; Oh, Hyuncheol; Hwang, Bang Yeon; Hirota, Hiroshi; Takahashi, Shunji; Kim, Bo Yeon; Osada, Hiroyuki; et al.
Graphical abstract: Abstract: During the chemical investigation of marine-derived fungus, an unusual diketopiperazine (DKP) alkaloid, haenamindole (1 ), was isolated from a culture of the marine-derived fungus Penicillium sp. KCB12F005. The structure of1, which possesses benzyl-hydroxypiperazindione and phenyl-pyrimidoindole rings system in the molecule, was elucidated by analysis of NMR and MS data. The stereochemistry of1 was determined by ROESY and advanced Marfey's method.